2015
DOI: 10.1002/prot.24778
|View full text |Cite
|
Sign up to set email alerts
|

Structural mapping of the coiled-coil domain of a bacterial condensin and comparative analyses across all domains of life suggest conserved features of SMC proteins

Abstract: The structural maintenance of chromosomes (SMC) proteins form the cores of multisubunit complexes that are required for the segregation and global organization of chromosomes in all domains of life. These proteins share a common domain structure in which N- and C- terminal regions pack against one another to form a globular ATPase domain. This "head" domain is connected to a central, globular, "hinge" or dimerization domain by a long, antiparallel coiled coil. To date, most efforts for structural characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Several attempts with full-length Smc coiled coils only yielded poorly diffracting crystals. Taking advantage of recently gained knowledge on the register of the Bs Smc coiled coil, we thus designed shorter Bs Smc fragments (Minnen et al., 2016, Waldman et al., 2015). A structure of a Smc middle segment, designated as Bs SmcCC2, comprising residues 246–379 and 793–929 connected via a short linker (Figure 2A), was solved by crystallography at a resolution of 3.2 Å (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Several attempts with full-length Smc coiled coils only yielded poorly diffracting crystals. Taking advantage of recently gained knowledge on the register of the Bs Smc coiled coil, we thus designed shorter Bs Smc fragments (Minnen et al., 2016, Waldman et al., 2015). A structure of a Smc middle segment, designated as Bs SmcCC2, comprising residues 246–379 and 793–929 connected via a short linker (Figure 2A), was solved by crystallography at a resolution of 3.2 Å (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of available disulfide register mapping and structural information (Bürmann et al., 2013, Minnen et al., 2016, Soh et al., 2015, Waldman et al., 2015), we designed a series of 258 successively shortened Smc constructs, covering most of the coiled coil at amino-acid resolution (Figure 2A). We then used a Golden Gate assembly driven allelic replacement strategy to regenerate the endogenous locus of a smc deletion strain with the synthetic variants (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the arm accommodated 70% of inserts in the input library, this fraction was reduced to 42% in the set of functional isolates (p < 0.001 by approximate permutation test). Furthermore, the distribution of coiled-coil inserts among the functional proteins was highly non-uniform, with hotspots close to the hinge and at the head- and hinge-proximal coiled-coil breaks, respectively (Minnen et al., 2016, Waldman et al., 2015). Insertions in the N-terminal helix were particularly rarely recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work revealed that the coiled coils are formed intra-molecularly by two anti-parallel strands11 and that their length of almost 50 nm, as well as the position of several coiled coil-interrupting regions are conserved596061. Compared with other coiled coil-containing proteins, the sequence of cohesin is remarkably conserved among metazoans but not among all eukaryotes62.…”
Section: Resultsmentioning
confidence: 99%